2012
DOI: 10.1007/s11999-012-2434-0
|View full text |Cite
|
Sign up to set email alerts
|

Culture-negative Periprosthetic Joint Infection Does Not Preclude Infection Control

Abstract: Background Periprosthetic joint infection (PJI) is a devastating complication after total joint arthroplasty. Lack of confirmation of an infecting organism poses a challenge with regard to the selection of an appropriate antibiotic agent and surgical treatment. It is unclear whether patients with negative cultures presumed to have infections achieve similar rates of infection-free survival as those with positive cultures. Questions/purposes The purposes of this study were (1) to report the infection control ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
46
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 22 publications
6
46
2
4
Order By: Relevance
“…In the present study, incidence of negative culture result was 42% (102 of 242 knees), which was substantially higher compared to other published series in the literature. 6,7,37,38 We suggest that this finding may be explained by higher incidence of previous intravenous and oral antibiotic treatment, which was consistent with the previous reports. that the culture-negative group showed significantly higher treatment success rates compared to the culture-positive group.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, incidence of negative culture result was 42% (102 of 242 knees), which was substantially higher compared to other published series in the literature. 6,7,37,38 We suggest that this finding may be explained by higher incidence of previous intravenous and oral antibiotic treatment, which was consistent with the previous reports. that the culture-negative group showed significantly higher treatment success rates compared to the culture-positive group.…”
Section: Discussionsupporting
confidence: 92%
“…Another study of 130 patients with periprosthetic joint infection demonstrated a 95% rate of eradication following reimplantation, but only a 68% rate when taking into account a reimplantation rate of 84.6% and those who either had been lost to follow-up or had died 28 . Despite having a lower reimplantation rate, the first stage as a starting point better represents the actual clinical course and explains the seemingly low infection eradication rates reported in the current study and previous reports from our institution [35][36][37][38] . It is also important to point out that, even for patients in the present study who ultimately underwent reimplantation, many underwent spacer exchange or surgical intervention for wound-related problems in the interstage period, with all of the inherent risks of added surgical procedures 19,39,40 .…”
Section: Discussionmentioning
confidence: 44%
“…Although all patients met the criteria established by the Musculoskeletal Infection Society for a periprosthetic infection, an organism was not identified in four patients. A recent study reported that despite extensive efforts including adequate clinical, radiographic, and intraoperative suspicion for PJI, cultures often have a high falsenegative rate, and culture-negative PJI is reported to occur in 7% to 9.5% of all infected arthroplasties [26]. Even if we presume that the four culture-negative patients were not truly infected and eliminate their results, our success rate is 87% versus 89% if included.…”
Section: Discussionmentioning
confidence: 74%